(untitled) (Research, Society and Development, 2022)
HIV is one of the most important diseases in the world, with vertical transmission being one of the most combated problems, especially after the introduction of antiretroviral therapy. However, mutations in HIV due to transmitted drug resistance (TDRM) can affect the effectiveness of the first line of empirical antiretroviral therapy (ART) schemes and its prevalence is believed to be increasing in the pediatric population and in pregnant women. Thus, the objective was to investigate, through an integrative review, the resistance transmitted to antiretrovirals in pregnant women and newborns by HIV-1, focusing on mutations and associated factors, through a literature review of the last 10 years, using the LILACS, MEDLINE and SCIELO databases, which make up the Virtual Health Library. As a result, there were 566 articles, of which 71 were pre-selected to be read in full, resulting in 14 approved articles. It was observed that many of the accepted articles were studied in Brazil, the United States and South Africa. The presence of transmitted resistance negatively affects the clinical efficacy of antiretroviral prophylaxis during future pregnancies, leading to a worsening of the infection and disease progression to child, when there is infection by this virus. Therefore, future research and public health policies should be directed to the monitoring of TDRM trends in prevalence and relationship with clinically relevant results in pregnant women and newborns with HIV-I.